B cell intrinsic and extrinsic factors impacting memory recall responses to SRBC challenge - Valeri, Viviana; Sochon, Akhésa; Ye, Chaoliang; Mao, Xinru; Lecoeuche, Damiana; Fillatreau, Simon; Weill, Jean-Claude; Reynaud, Claude-Agnès; Hao, Yi (Frontiers in Immunology, 2022)
MBCs (MBCs) generated in T-dependent immune responses can persist for a lifetime and rapidly react upon secondary antigen exposure to differentiate into plasma cells (PCs) and/or to improve the affinity of their BCR through new rounds of hypermutation in germinal centers (GCs). The fate of a MBC in secondary immune reactions appears to depend upon multiple parameters, whose understanding is mandatory for the design of efficient vaccine strategies. We followed the behavior of MBCs in recall responses to SRBCs using an inducible AID fate mapping mouse model in which B cells engaged in a germinal center (GC) response are irreversibly labeled upon simultaneous tamoxifen ingestion and immunization. We used different schemes of mouse immunization and tamoxifen feeding in adoptive-transfer experiments of total splenic B cells into congenic mice that have been pre-immunized or not, to assess the contribution of the different effector subsets in a physiological competitive context. We were able to show that naive B cells can differentiate into GC B cells with kinetics similar to MBCs in the presence of previously activated T follicular helper (TFH) cells and a primed microenvironment. We also showed that MBCs are recruited into secondary GCs, together with naive B cells. In contrast, PC differentiation, which dominated secondary MBC responses, was not dependent upon a previous TFH activation. We observed that the presence of persisting germinal centers and circulating antibody levels are key factors determining the germinal center versus plasma cell fate in a recall response. Notably, disruption of persistent germinal center structures by a lymphotoxin beta-receptor fusion protein or a longer timing between the prime and the boost, which correlated with reduced antigen-specific immunoglobulin levels in serum, were two conditions with an opposite impact, respectively inhibiting or promoting a GC fate for MBCs. Altogether, these studies highlight the complexity of recall responses, whose outcome varies according to immunization contexts.